EFEKTIFTAS MENGUNYAH BUAH BERSERAT DAN BERAIR TERHADAP KUANTITAS BAKTERI STREPTOCOCCUS MUTANS PADA ANAK KEBUTUHAN KHUSUS - Tri Wiyatini; Endah Aryati Ekoningtyas; Prasko Prasko (Jurnal Kesehatan Gigi, 2016)
TITLEThe effectiveness of chewing stringy and watery fruits against the quantity of Streptococcus mutans in children with special needsABSTRACTChildren who suffer from mental retardation associated with muscle coordination resulted in delays on the development of movement (motoric), speech, and limitations adjust to the environment. The disorder is also added to the difficulties of children to be able to maintain healthy teeth and mouth independently and are less active mouth muscles to get a good natural cleansing. The process of chewing fibrous foods will stimulate and increase saliva production. The apple is a fibrousfruit which can be obtained on the market. And apple has the ability to self-cleansing effect. This study aims to determine the effect of chewing an apple to the quantity of Streptococcus mutans bacteria in children with special needsThis type of research is descriptive. The method used in this study is a quasi experimental and design studies carried out by one group pretest and posttest. In this study, a sample calculation of the number of bacteria before and after chewing apples in saliva using Total Plate Count. Samples were 15 students from elementary classes I-VI mild mental retardation in special schools amounted foundation Widya Bhakti Semarang.The results showed statisticfrom  paired t-test that there are effective chew of fibrousand juicy fruit on the quantity of bacteria Streptococcus mutans in a special needs child, and from the analysis of the data showed a significant difference with the t value of 3,778 df (degrees of freedom) and p value = 0.002 (p 0.05). Keywords : fruit fibrous watery, streptococcus mutans quantity